2018
DOI: 10.17660/ejhs.2018/83.1.1
|View full text |Cite
|
Sign up to set email alerts
|

How does peach fruit set on sylleptic shoots borne on epicormics compare with fruit set on proleptic shoots?

Abstract: Proleptic and epicormic shoots on peach (Prunus persica) have different growth characteristics that have management implications for peach production. Proleptic shoots arise from buds after a dormant period, and are made up mostly of preformed nodes and organs which exist in dormant buds and extend after bud-break. Epicormic shoots (also known as 'water sprouts') arise from preventitious meristems without the formation of a bud and are characterized by vigorous, upright growth. They are usually stimulated by h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Gradziel [33] described that a desirable almond tree ideotype may present axillary shoots equally distributed along the axis. In peach trees, floral buds are developed in higher numbers on proleptic shoots than sylleptic shoots [16]. This suggests that a commercial ideotype should not produce too many sylleptic shoots as these might be at the expense of fruiting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gradziel [33] described that a desirable almond tree ideotype may present axillary shoots equally distributed along the axis. In peach trees, floral buds are developed in higher numbers on proleptic shoots than sylleptic shoots [16]. This suggests that a commercial ideotype should not produce too many sylleptic shoots as these might be at the expense of fruiting.…”
Section: Discussionmentioning
confidence: 99%
“…The formation of proleptic and sylleptic shoots has also been analyzed under different environments or experimental treatments, for example, water deficiency or pruning [14,15]. In peach (P. persica (L.) Batsch), it has been reported that more floral buds are produced on proleptic than sylleptic shoots [16]. Therefore, the overall proportion of these shoot types can largely alter the commercial viability of Prunus cultivars, including almond.…”
Section: Introductionmentioning
confidence: 99%
“…Since proleptic shoots are regarded as more productive [52,53], traditional culture techniques commonly include pruning sylleptic shoots. Rosaceae fruit trees were domesticated as early as during the Neolithic and therefore many training methods have been developed to maximize fruit size, sun exposure, aeration, or to ease harvesting among other factors.…”
Section: Applementioning
confidence: 99%